Sex, Slavery and the Trafficked Woman : Myths and Misconceptions about Trafficking and Its Victims. - Vijeyarasa, Ramona. (Gender in a Global/Local World Series, 2016)
Sex, Slavery and the Trafficked Woman is a go-to text for readers who seek a comprehensive overview of the meaning of 'human trafficking' and current debates and perspectives on the issue. It presents a more nuanced understanding of human trafficking and its victims by examining - and challenging - the conventional assumptions that sit at the heart of mainstream approaches to the topic. A pioneering study, the arguments made in this book are largely drawn from the author's fieldwork in Ukraine, Vietnam and Ghana. The author demonstrates to readers how a law enforcement and criminal justice-oriented approach to trafficking has developed at the expense of a migration and human rights perspective. She highlights the importance of viewing trafficking within a broad spectrum of migratory movement. The author contests the coerced, female victim archetype as stereotypical and challenges the reader to understand trafficking in an alternative manner, introducing the counterintuitive concept of the 'voluntary victim'. Overall, this text provides readers of migration and development, gender studies, women's rights and international law a comprehensive and multidisciplinary analysis of the concept of trafficking.